Investigation of the Effects of a1-Adrenoceptor Antagonism and L-Type Calcium Channel Blockade on Ejaculation and Vas Deferens and Seminal Vesicle Contractility In Vitro - de Almeida Kiguti, Luiz Ricardo [UNESP]; Pupo, Andre Sampaio [UNESP] (Wiley-Blackwell, 2012)
Introduction. Premature ejaculation is one of the most common male sexual dysfunctions. Current pharmacological treatments involve reduction in penile sensitivity by local anesthetics or increase of ejaculatory threshold by selective serotonin reuptake inhibitors. a1-Adrenoceptors (a1-ARs) and L-type calcium channels are expressed in the smooth muscles of the male reproductive tract, and their activations play an important role in the physiological events involved in the seminal emission phase of ejaculation.Aim. To evaluate if the inhibition of the contractility of the vas deferens and seminal vesicle by alpha(1)-AR antagonism or the L-type calcium channel blockade can delay ejaculation.Methods. The effects of the alpha(1)-AR antagonist tamsulosin and of the L-type calcium channel blockers, nifedipine and (S)-(+)-niguldipine, on contractions induced by norepinephrine in the rat vas deferens and seminal vesicles in vitro and on the ejaculation latency of male rats in behavioral mating tests were evaluated.Main Outcome Measure. Tension development of vas deferens and seminal vesicles in response to norepinephrine in vitro and behavioral mating parameters were quantified.Results. Tension development of vas deferens and seminal vesicle to alpha(1)-AR activation was significantly inhibited by tamsulosin, nifedipine, and (S)-(+)-niguldipine. Tamsulosin displayed insurmountable antagonism of contractions induced by norepinephrine in the rat vas deferens and seminal vesicle. Ejaculation latency of male rats was not modified by tamsulosin, nifedipine, or (S)-(+)-niguldipine; however, both the number and weight of the seminal plugs recovered from female rats mated with male rats treated with tamsulosin were significantly reduced.Conclusion. Seminal emission impairment by inhibition of vas deferens or seminal vesicle contractility by L-type calcium channel blockade or alpha(1)-AR antagonism is not able to delay the ejaculation. de Almeida Kiguti LR and Pupo AS. Investigation of the effects of alpha(1)-adrenoceptor antagonism and L-type calcium channel blockade on ejaculation and vas deferens and seminal vesicle contractility in vitro. J Sex Med 2012; 9: 159-168.
Keywords: Premature Ejaculation; Vas Deferens; Seminal Vesicle; Ejaculatory Latency; a1-Adrenoceptors; L-Type Calcium Channels